Предмет: Алгебра,
автор: hsbwkq
(x^2 + 3x) * (x^2 +3x -17) + 60 =0
Ответы
Автор ответа:
0
(x²+3x)×(x²+3x-17)+60=0
x⁴+3x³+3x³+6x²-17x²-41x+60=0
x⁴-5x²-41x+60=0
x⁴-5x²-41x=0-60
x⁴-5x²-41x=-60
Далее нужно знать переменную x для вычисления
x⁴+3x³+3x³+6x²-17x²-41x+60=0
x⁴-5x²-41x+60=0
x⁴-5x²-41x=0-60
x⁴-5x²-41x=-60
Далее нужно знать переменную x для вычисления
Похожие вопросы
Предмет: Русский язык,
автор: Uliana290710
Предмет: Английский язык,
автор: midariikishima1
Предмет: Математика,
автор: aadeuir
Предмет: Физика,
автор: mainsharabi
Предмет: Информатика,
автор: yuliyamalkova